TRANSFORMATION OF EXPERIENTIAL LEARNING THROUGH THE HUNTING TOURIST PROGRAM IN FULL DAY SCHOOL CLASSES - Muhammad Khoirul Mala; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The madrasah education system with a full day school model faces challenges of learning saturation due to long duration and monotonous conventional methods, thus requiring learning innovations capable of creating meaningful, contextual, and enjoyable learning experiences. In response to this condition, the Hunting Tourist Program was developed as an experiential learning transformation model that utilizes interaction with tourists as an authentic learning resource. This study examines the transformation of experiential learning through the Hunting Tourist Program in the full day class. The research objectives are to describe program implementation, analyze its impact on students’ language competencies, and identify management factors contributing to program effectiveness. This study employs a library research method with a qualitative content analysis approach. Data were collected through documentation and literature review comprising scientific journal articles, books, and relevant prior research. The findings indicate that experiential learning through the Hunting Tourist Program successfully shifted the learning paradigm from teacher-centered to student-centered, enhanced students’ language competencies (multilingual communication skills), critical thinking, social intelligence, and character development. This program aligns with Kolb’s experiential learning cycle and supports the Merdeka Curriculum’s objectives in developing holistic learner competencies, while offering an innovative solution to overcome learning boredom in the full day school system.